The demand model of electric field strength on microelectrode designed for ac electrokinetic applications - Md Yunus, Nurul Amziah; Jaafar, Haslina; Abdul Halin, Izhal; Jasni, Jasronita (IEEE (IEEE Xplore), 2014)
This paper presents an investigation of electric field strength using the Multi-Physics Finite Element Solution Environment for Partial Differential Equations, FlexPDE. It is to give an idea on the flow of particles in lab on a chip (LoC) and bioMEMS devices when they passed through the active microelectrode array using one of the AC electrokinetic techniques that is dielectrophoresis. The field strength regions can give an overview of particle motion either to high electric field strength or to low electric field strength in relation to the dielectrophoretic force. The results from this investigation will be used to justify the direction of particles flow in the LoC device during experimental work.